Chemotherapy for Non-Small Cell Lung Cancer in the Intensive Care Unit. (2021) - Nasser, Abdullah; Hartwick, Michael; Kyeremanteng, Kwadwo; Wheatley-Price, Paul
Highlights: Usual standard of care for NSCLC patients in the ICU is palliation. Mucinous NSCLC can present with copious mucoid secretions. Cytotoxic chemotherapy can achieve rapid response in mucinous NSCLC. Abstract: Background: patients with non-small-cell lung cancer (NSCLC) admitted to the intensive care unit have poor prognosis. There is limited data on cytotoxic chemotherapy in this setting. The standard of care for these patients is usually best supportive care. Case: 60-year-old previously healthy female was admitted to the ICU with newly diagnosed mucinous adenocarcinoma of the lung. She received cisplatin and pemetrexed while intubated and mechanically ventilated. She was extubated a week later and discharged home after achieving an excellent radiographic and clinical response. Discussion: in select patients with NSCLC admitted to the ICU due to complications from their malignancy, a trial of cytotoxic chemotherapy may be reasonable. To our knowledge, this is the first case of mucinous NSCLC treated in the ICU.